Social Media Marketing, Brand Awareness, and Consumer Reviews in Gen Z Skincare Purchase Decisions - Theresia Aurora; Arbi Siti Rabiah (Score: Jurnal Lentera Manajemen Pemasaran, 2026)
This study aims to analyze the influence of Social Media Marketing, Brand Awareness, and Customer Reviews on Purchase Decisions for local skincare products among Generation Z in the Jabodetabek area. The data collection method was carried out by distributing questionnaires using Google Form media, with a sample size of 301 respondents. The data analysis technique used was multiple linear regression analysis, with the help of SPSS version 25 software. The results of the study showed that Social Media Marketing, Brand Awareness, and Customer Reviews had a positive and significant effect on purchase decisions (Purchase Decision) for local skincare products. This finding indicates that these three variables are important factors that need to be considered by business actors in increasing Gen Z consumers' purchasing decisions for local skincare products.